Recent Developments in Catalytic Reductive Etherifications - Zaharani, Lia; Nader Ghaffari Khaligh (Malaysian Catalysis-An International Journal, 2022)
Ether derivatives are versatile organic compounds and have been applied in various fields of academia and the chemical industry. Therefore, it is highly desirable to create procedures for their manufacture that are more efficient and sustainable. Catalytic reductive etherification with carbonyl moiety such as ketones/ aldehydes and carboxylic acid derivatives has recently been recognized as a possible tool among the several techniques reported for ether production. These procedures offer promising methods to selectively produce ethers with higher molecular structures, both symmetrical and asymmetrical. This Review provides an update on current developments in the field of catalytic reductive etherification, which synthesize ethers utilising an alcohol and an aldehyde substrate. Applications for organic synthesis and catalyst design are given special attention.